2007
DOI: 10.2298/bah0702267w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of genotype on muscle fibre characteristics of m. longissimus lumborum of fatteners

Abstract: For histochemical analysis of muscle fibre types the activity of dehydrogenase NADH 2 (diaphorase) was detected using specific histochemical testes. The results of the current histochemical investigations showed that genotypes of fatteners can influence on histochemical composition of the muscle fibre types -especially on percentage and size of muscle fibre. These changes can have some influence on meat consumption quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…To visualize the blood capillaries the α-amylase-periodic acid schiff (α-amylase-PAS) method was used; such reaction stains the basal membrane of the capillaries. The fibre type composition of different skeletal muscles could be one of the most important factors influencing the biochemical events associated with their conversion to meat (Wojtysiak et al 2007). Recent evidence implies that fibre type proportions play a role in meat quality; in pigs it has been suggested that slow oxidative fibres contribute to both juiciness and tenderness (Fonseca et al 2003).…”
mentioning
confidence: 99%
“…To visualize the blood capillaries the α-amylase-periodic acid schiff (α-amylase-PAS) method was used; such reaction stains the basal membrane of the capillaries. The fibre type composition of different skeletal muscles could be one of the most important factors influencing the biochemical events associated with their conversion to meat (Wojtysiak et al 2007). Recent evidence implies that fibre type proportions play a role in meat quality; in pigs it has been suggested that slow oxidative fibres contribute to both juiciness and tenderness (Fonseca et al 2003).…”
mentioning
confidence: 99%
“…Ruusunen and Puolanne [28], who investigated the muscles of Hampshire, Landrace and Yorkshire pigs, found that the muscles of Hampshire pigs were more oxidative compared to those of the others pigs, and showed that variations in muscle fibre composition in pigs within the breeds were larger than the average variations between the breeds. Muscle fibre composition is influenced by age/body weight and the growth rate of animals [33,56,57]. Many researchers have examined the relationship between muscle fibre type characteristics and meat quality [51,[58][59][60].…”
Section: Resultsmentioning
confidence: 99%